Peran Fasilitas Sanitasi dan Personal Hygiene dalam Kelaikan Hygiene Sanitasi Warung Makan di Wanareja Kabupaten Cilacap - Rokhman, Oman (Medical : Jurnal Kesehatan dan Kedokteran, 2024)
Hygienic food processing facilities are essential to prevent the risk of disease transmission through food consumption. In Wanareja Village, the working area of Wanareja 1 Community Health Center in 2022, there were 34 food processing facilities, of which only 61.8% met sanitation standards. Field observations revealed that some food establishments neglected sanitation facilities, while personal hygiene among food handlers was often overlooked. This study employed a quantitative approach to examine the role of sanitation facilities and personal hygiene among food handlers in achieving hygiene and sanitation standards at food stalls in Wanareja, Cilacap District. The population in this study consisted of 24 food stalls and 42 food handlers. The sample for food stalls was taken using total sampling namely 24 food stalls, while the number of food handlers was determined using the slovin formula, namely 24 food handlers. Data analysis was performed using the Fisher Exact test to examine the relationship between variables. The results of the Fisher Exact test showed a significant role between food stall sanitation facilities and food stall hygiene and sanitation standards (p = 0.012; α = 0.05). Conversely, no significant role was found between food handler personal hygiene and the achievement of food stall hygiene and sanitation standards (p = 1.000; α = 0.05). These findings indicate that sanitation facilities play an important role in determining the hygiene standards of food stalls, while the personal hygiene of food handlers in this context does not have a significant influence. Therefore, efforts to improve sanitation facilities should be a top priority in improving hygiene and health standards at food processing sites in Wanareja Village.